Improved uniform degree of multi-layer interlaminar bonding strength for composite laminate. (September 2017) - Zhao, Pan; Shirinzadeh, Bijan; Shi, Yaoyao; Cheuk, Simeon; Clark, Leon
Due to their high strength-to-weight and stiffness-to-weight ratios, composite materials are widely used in the aerospace industry. As a key factor for the placement process, the compaction force directly affects the product performance by changing the interlaminar bonding strength. Besides the magnitude of the interlaminar bonding strength, the uniformity degree of the bonding strength for each contact interface also affects the overall structural rigidity of laminates. This study is aimed at analyzing and optimizing the compaction force when using a rubber roller to produce a composite product with uniform interlaminar bonding strength. The amount in which the compaction force from a rubber roller on the current layer influences the bonding strength of the layers underneath is investigated, and methods for optimizing the interlaminar bonding strength are developed and experimentally demonstrated.